Two Approaches for Interpreting Tsu Chen Chao’s Theology - Changping ZHA (Journal of Research for Christianity in China (JRCC), 2024)
Based mainly on the texts written by Lam Wing-hung, Ying Fuk-tsang, Winfried Glüer and so on, this article suggests that there are relevant and different approaches for interpreting Tsu Chen Chao (1888–1979)’s theology in Chinese scholarship today that focus on his discussions of the relationship between Christianity and Chinese culture as well as society in the 1920s, 1930s and 1940s. The approaches of interpretation have a witness for the general feature of hermeneutics that in some degree the interpretive approaches of object will prescribe the interpretive approaches of its subjects.